Produtos naturais e o manejo das lesões não cariosas: avaliação laboratorial, exploratória e revisão da literatura - Leal, Isabelly de Carvalho (2024)
Non-carious lesions are characterized by mineral loss of the dental substrate without bacterial involvement. Since they present a multifactorial condition, the formulation of personalized preventive strategies is only possible when the etiology of the lesion is correctly defined. This study consists of four chapters, the first of which aimed to analyze, through a cross-sectional and exploratory study, the knowledge of dental surgeons (DS) about diagnostic and treatment strategies for erosive tooth wear. A questionnaire was applied through the Google Forms platform and 315 responses were obtained. Brazilian DS appear to have good knowledge about the necessary guidelines for patients with erosion lesions. However, diagnostic management is largely neglected and professionals do not appear to be aware of recent guidelines that minimally invasive approaches are preferable for treatment. The second chapter aimed to investigate the influence of the knowledge profile of DS on decision-making regarding treatment for erosive tooth wear. The same sample from chapter 2 was dichotomized into professionals with high and low levels of knowledge according to the responses recorded in the questionnaire to perform univariate and multivariate regressions. The results show that 86.4% of the professionals had a low level of knowledge about the use of the specific scoring system for diagnosing erosive lesions and/or about obtaining a dietary history. In addition, professionals with a high level of knowledge were more likely to indicate non-restorative treatments for cases of erosive lesions. The third chapter aimed to evaluate, through an in vitro and randomized study, the effect of hesperidin (HPN) on dentin permeability. Permeability was evaluated at three times: after opening the tubules with 17% EDTA for 2 min, after application of treatments for 5 min [distilled water, potassium oxalate (OXG), HPN 3%, 5% and 10%] and after erosive/abrasive cycling for 3 days. HPN 5% showed a significant reduction in post-cycling permeability (p<0.05), but its effect was not superior to OXG or distilled water. The fourth chapter aimed to systematically review in situ studies to verify the effect of different natural products in preventing erosive and abrasive wear. A literature review was conducted using search strategies developed for major databases and gray literature. Of a total of 1,900 articles, 8 were selected, including 224 samples treated with polyphenols and 224 control samples. Considering the studies included in this review, it was observed that polyphenols tend to promote a reduction in erosive/abrasive wear compared to control groups. Thus, it can be concluded that natural extracts have the ability to prevent erosive/abrasive wear in situ, with HPN 5% being able to reduce dentin permeability in vitro. Furthermore, DS seem to have good knowledge about the guidelines needed for patients with dental erosion lesions, but not about the diagnostic and treatment guidelines; and professionals with a high level of knowledge were more likely to indicate non-restorative treatments for cases of erosive lesions.